I pozzetti rituali sul fronte della Basilica Iulia e la riscoperta dei cd. calicetti di Giacomo Boni - Montali, Ivana (Römische Mitteilungen, 2024)
The contribution focuses on the pits located along the north long side of the Basilica Iulia, identified during the investigations conducted by Giacomo Boni in 1901. Built on the systematic analysis of the archive documentation and the study of the archaeological finds collected by Boni, this paper reconstructs the chronology of construction, the use and abandonment of the pits, and then discusses their original function in the wider framework of the use of the Roman Forum during the late Republican and Augustan ages. In particular, the analysis focuses on the pottery finds, and on a group of still unpublished and unusual vessels interpreted as miniaturized thymiateria, locally produced in Rome after southern Greek originals. Questions as to their prototypes, use and significance in the religious life of Rome and their connection with the abandonments of the pits in the Augustan period are all discussed.